Evaluated of Annular Baffle on Dynamic behavior of Elevated Liquid Storage Tanks under Blast Loading - Farhoud Kalateh (Iranian Society of Structrual Engineering (ISSE), 2020)
In last decades with an increase in the number of terrorist attacks and other unintentional explosions, the study of blast loading and response of infrastructures have gained much importance. Elevated liquid storage tanks are one of the major infrastructures that play important role in industries. Liquid storage structures can use for the storage of water, milk, liquid petroleum and chemicals in industries. Blast loading on liquid storage structures may lead to disaster due to water crisis. Hence, understanding the dynamic behavior of liquid storage structures under blast loading through numerical simulations is of utmost importance. In the present study, three dimensional (3D) finite element (FE) simulations of a steel water storage elevated tank with annular baffle that put in the specific height of tank’ s wall subjected to blast loading is investigated using the FE software ABAQUS. The coupled Euler–Lagrange (CEL) formulation in ABAQUS has been adopted herein which has the advantage of considering the coupling of structural mechanics and fluid mechanics fundamental equations. Three different aspect ratio (H/R) are considered in the present study and two different water levels, i.e., full tank and half full tank are considered. Obtained results show that baffle reduces overturning moments and sloshing in both cases of full and half full tanks.